Analisis Infografis Baliho Kesehatan Masa Pandemi Covid-19 di Kota Padangsidimpuan Ditinjau dari Tipografi, Warna dan Fungsi - Zakiyah Rahman Nasution; Daulat Saragi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
Billboards are communication media resulting from graphic design with the aim of conveying information. This study aims to determine the type of typography, color character and message function on COVID-19 billboards in Padangsidimpuan City. This research was conducted from March to May 2021. This study used qualitative methods with qualitative descriptive data analysis techniques. The total population is 5 billboards. The sampling technique used was total sampling, that is, the entire population was sampled. The findings in this study indicate that overall the COVID-19 billboards in Padangsidimpuan City are good in terms of typography, color and message function. The type of font used relates to the level of ease of reading, the size of the letters used relates to readability. The typography and colors used are tailored to the theme. The colors used give emphasis to billboards so that they create contrast. The message functions contained in the billboards are a warning function, a persuasive function, and an educational function.